Teaching Precarity, Resistance, and Community: Rohini Mohan's The Seasons of Trouble and Genocide Pedagogy. Issue 3 (2nd October 2018) - Clemens, Colleen Lutz
Abstract: Testimonials of the Sri Lankan war are just coming to light as people begin to feel like they can tell their stories of being kidnapped into forced military service, fleeing bombings, searching for loved ones, and being displaced in their own nation. This paper argues for the importance of studying the Sri Lankan civil war and its aftermath in the context of genocide pedagogy where students can be given the opportunity to ask critical questions: Why do wars start? How do people that see each other as friendly neighbors come to believe those same neighbors are the enemy in a short period of time? How does genocide start and end? Who controls the narrative during wartime? What does it mean for children to grow up during a war? What does it mean to be a displaced person on the same soil one used to cultivate? How does a nation come back together and heal while simultaneously learning the stories that were kept silent during the decades of war? If we as teachers can get students to consider these challenging questions early in their academic career, our students will be well-positioned to tangle with these issues when it is up to them to work within geopolitical conflicts that arise during their adult lives. Teachers who are interested in learning about the historical, political, and cultural foundations of the war will find Rohini Mohan's The Seasons of Trouble: Life Amid the Ruins of Sri Lanka's Civil War an invaluable pedagogical tool.